Penerapan Model Pembelajaran Two Stay Two Stray Untuk Meningkatkan Hasil Belajar Dan Keaktifan Belajar Siswa Pada Materi Teks Eksposisi - Hadijah Hadijah (Journal of Classroom Action Research, 2023)
The purpose of this study was to improve student learning outcomes and activeness in exposition text material in class X MIA 4 SMA Negeri 3 Sumbawa Besar Odd Semester 2019/2020 Academic Year through the application of the Two Stay Two Stray learning model. This research is included in the form of Classroom Action Research (CAR) and is carried out in 2 cycles, namely Cycle I and Cycle II. Each cycle consists of planning, action, observation, and reflection. The data to be collected in this study is on the research aspect, namely the application of the two stay two stray learning model and the results of learning Indonesian students and the activeness of student learning. The results of the study showed that: (1) The implementation of learning in the Indonesian language subject material for exposition text content using cooperative learning type two stay two stray in class X MIA 4 SMA Negeri 3 Sumbawa Besar can increase student activity. This is based on observations of all indicators that have been determined in cycle I showing an average student activity of 68.55%, the category is sufficient to increase to 81.86%, the good category in cycle II has exceeded the indicators of completeness of activities classically defined in this study, namely 75% good category. The increase in student activity from cycle I to cycle II was 13.31%; (2) Implementation of learning in the Indonesian language subject material for exposition text content using cooperative learning type two stay two stray in class X MIA 4 SMA Negeri 3 Sumbawa Besar can improve student learning outcomes. This is based on the results of the posttest in cycle I obtained an average value of 79.19 with the percentage of students who completed KKM by 77.42% experienced an increase in cycle II with an average value of 81.48 and the percentage of students who completed KKM was 87 .10% has exceeded the classical success indicator set in the study, namely 85%.